Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.187
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Value of Information in Medical Notes

Abstract: Machine learning models depend on the quality of input data. As electronic health records are widely adopted, the amount of data in health care is growing, along with complaints about the quality of medical notes. We use two prediction tasks, readmission prediction and in-hospital mortality prediction, to characterize the value of information in medical notes. We show that as a whole, medical notes only provide additional predictive power over structured information in readmission prediction. We further propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Comparing the distribution of the ‘Baseline + Patient-Level Clinician’ model (mean: 0.80; SE: 0.004) to the distribution of the ‘Baseline’ model (mean: 0.70; SE: 0.006), the former distribution significantly dominates the latter, evidencing that there are features predictive of prostate cancer recurrence in patient notes. This is in line with Hsu et al’s work 52 on the readmission prediction task and other studies 17,51 . Further comparing the distribution of the ‘Baseline + Patient-Level Clinician’ model to the ‘Baseline + Automated NLP’ model (mean: 0.74; SE: 0.006), we conclude that the patient-level CFG process of leveraging extensive clinical expertise to identify and create patient-level features is able to extract more signal from the progress notes, compared to the AFG method via NLP.…”
Section: Resultssupporting
confidence: 92%
“…Comparing the distribution of the ‘Baseline + Patient-Level Clinician’ model (mean: 0.80; SE: 0.004) to the distribution of the ‘Baseline’ model (mean: 0.70; SE: 0.006), the former distribution significantly dominates the latter, evidencing that there are features predictive of prostate cancer recurrence in patient notes. This is in line with Hsu et al’s work 52 on the readmission prediction task and other studies 17,51 . Further comparing the distribution of the ‘Baseline + Patient-Level Clinician’ model to the ‘Baseline + Automated NLP’ model (mean: 0.74; SE: 0.006), we conclude that the patient-level CFG process of leveraging extensive clinical expertise to identify and create patient-level features is able to extract more signal from the progress notes, compared to the AFG method via NLP.…”
Section: Resultssupporting
confidence: 92%
“…The increasing trend of using textual data for summarization might be attributed to the improvement of NLP, the improved computing power required for some NLP tasks, and the results published by Van Vleck et al [ 158 ], who claimed that a significant portion of patient information lies in clinical notes. In contrast, Hsu et al [ 111 ] challenged this hypothesis by presenting experiments to predict some clinical measures (eg, hospital readmission and mortality) using textual and structured patient information sources. They concluded that textual sources have little predictive power for the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we will explore various approaches to preprocessing the clinical notes, focusing on different ways to select the terms used to train the topic models (e.g., based on term frequency, term frequency-inverse document frequency weights, and named entity recognition). We will also train topic models on different clinical note types and sections, based on evidence that predicting clinical outcomes from medical notes may be improved when more relevant note types or parts are used [ 188 ]. To evaluate these approaches, we will examine associations between emerging topics and the available structured data (i.e., as a form of external validation), as well as perform human-in-the loop evaluations of topic coherence [ 189 ].…”
Section: Methodsmentioning
confidence: 99%